Experimental characterization and numerical analysis of the influence of the CED coating process on viscous fingering formation in hybrid-jointed mixed structures - Al Trjman, Mohamad; Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Riese, Julia (The Journal of Adhesion)
The joining of dissimilar materials, such as steel and aluminum, entails significant challenges during thermal curing processes due to differing coefficients of thermal expansion. This study addresses the formation of “viscous fingering” instabilities in structural adhesive joints, which are induced by thermally driven relative displacements during the liquid phase of the adhesive. Using a component-like specimen “bridge specimen,” the dependency of this phenomenon on process temperature and structural stiffness (rivet distance) was characterized. Experimental results reveal that while the relative displacement scales cubically with the free buckling length, the resulting adhesive area reduction follows an exponential trend, leading to a loss of effective bond area of up to 79%, which significantly compromises the joint strength in automotive applications. To predict these process-induced defects, a thermo-chemo-viscoelastic-viscoplastic adhesive model implemented in LS-DYNA was applied. The model combines curing kinetics, viscoelastic relaxation, and pressure-dependent plasticity and features a geometric damage parameter (D) that captures the adhesive area reduction caused by viscous fingering as an exponential function of the accumulated normal strain in the liquid phase. This damage parameter, calibrated on base-specimen level, was transferred to the component geometry. The simulation demonstrated high predictive accuracy with a maximum deviation of the adhesive area reduction of 3.1% compared to experimental data. This validates the model’s capability to predict manufacturing-induced damage in complex hybrid structures solely based on thermal boundary conditions.
Keywords: Adhesive area reduction; CED coating process; delta alpha problem; epoxy structural adhesive; influence of manufacture; multi-material design; numerical simulation (FEM); relative displacements; viscous fingering (saffman-taylor-instability).

Viscous fingering in adhesive bonding - Al Trjman, Mohamad; Salten, Alexander Heinrich Johannes; Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Riese, Julia; Kenig, Eugeny (International Journal of Adhesion and Adhesives)

Methodenentwicklung zur Simulation des Viscous Fingering in Klebverbindungen von stahlintensiven Mischbaustrukturen - Al Trjman, Mohamad; Meschut, Gerson; Salten, Alexander Heinrich Johannes; Kenig, Eugeny Y.

Method development (modelling, simulation, characterisation) in adhesive bonding technology - Beule, Felix; Al Trjman, Mohamad; Teutenberg, Dominik; Meschut, Gerson

Simulation des „viscous fingering“ Effektes in Klebverbindungen - Salten, Alexander Heinrich Johannes; Al Trjman, Mohamad; Meschut, Gerson; Kenig, Eugeny Y.

Methodenentwicklung zur Simulation des Viscous Fingering in Klebverbindungen von stahlintensiven Mischbaustrukturen - Al Trjman, Mohamad; Meschut, Gerson; Salten, Alexander Heinrich Johannes; Kenig, Eugeny Y.

DigiBody - Digitale Prozesskette zur Abbildung und Optimierung der Fügetechnik im Rohbau - Jamei, Said; Döller, Norbert; Lossau, Sebastian; Beule, Felix; Al Trjman, Mohamad; Aubel, Tobias; Meschut, Gerson; Sommer, Daniel; Facciotto, Silvio; Droste, Alexander; Haufe, Andre; Helbig, Martin; et al. (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

A new viscoelastic-viscoplastic constitutive formulation in LS-DYNA to model adhesives during the complete manufacturing-crashworthiness process chain - Klöppel, Thomas; Haufe, Andre; Helbig, Martin; Liebold, Christian; Beule, Felix; Al Trjman, Mohamad; Aubel, Tobias; Meschut, Gerson; Jamei, Said; Fürle, Fabian; Lossau, Sebastian; Droste, Alexander; et al. (4a-Technologietage 2022)